ON THE RELIGIOUS AND SPIRITUAL LIFE OF THE ANCIENT POPULATION - Furkat Eshboevich Toshboev; Utkir Rakhmat ugli Ravshanov (Bright Mind Publishing, 2025)
In this article, the authors provide information about the religious and spiritual life of the ancient population. The authors emphasize that the ancient population was characterized by clan beliefs, totemic cults associated with natural phenomena, deification of nature, as well as shamanic beliefs mixed with animism and totemism. One of the most important aspects of these religious beliefs is that they have a unifying effect on communities.
Keywords: Fire, wild birds, sun worship, rock paintings, mountain goat, burial rite, Scythian-Siberian method, candles, shamanism, Gulba, wolf, shamanism. Suzmoilota.